A case report of apatinib in treating osteosarcoma with pulmonary metastases. Issue 15 (April 2017) - Zhou, Yong; Zhang, Wengeng; Tang, Fan; Luo, Yi; Min, Li; Zhang, Wenli; Shi, Rui; Duan, Hong; Tu, Chongqi
Abstract: Rationale: Osteosarcoma is the most common malignant bone tumor in children and adolescents. Pulmonary metastases lead to a significantly increased risk of death. Apatinib, a new potent oral small-molecule tyrosine kinase inhibitor targeting the intracellular domain of vascular endothelial growth factor receptor 2 (VEGFR-2), shows survival benefits in treating advanced or metastatic gastric adenocarcinoma, non-squamous non-small cell lung cancer and metastatic breast cancer. However, its efficacy in metastatic osteosarcoma has not been reported yet. Patient concerns: Herein, we presented a 50-year-old man patient who visited hospital due to local bone pain in the left leg. Diagnoses: He was initially diagnosed with osteoblastic osteosarcoma. Interventions: The patient suffered repeated resection surgeries but developed multiple lung metastases. Positive staining for CD31, CD34, and VEGFR-2 were detected in the tumor section. As he refused to receive chemotherapy due to concerns regarding the chemotherapy toxicities and sorafenib due to high cost, apatinib was given at a dose of 500 mg daily. Outcomes: Eleven months following apatinib administration, the patient achieved a partial response according to the RECIST 1.1 standard. No severe toxicity or drug-related side effect was observed during the treatment. Lessons: Therefore, apatinib could be a new option for the treatment of metastatic osteosarcoma. Clinical trials are required to further confirm the efficacy and safety of apatinib in treating pulmonary metastases from osteosarcoma.